An intensive audit on 250 patients of advanced ovarian cancer to improve quality of care in a tertiary referral oncology centre in India - Ray, M. D.; S. Deo, S. V.; Pramanik, Raja; N., Premanand (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: A clinical audit provides the framework to improve the quality of patient care in a systematic way. In this study, we intensively audited our 250 advanced epithelial ovarian cancer (EOC) patients aiming to improve our patient care. Methods: Ambispective study of 250 patients of advanced EOC was done from our prospectively maintained computerized database in the department of surgical oncology, AIIMS, New Delhi from 2013 to 2020.We audited the demographic profile, treatment patterns, perioperative and survival outcomes in different subgroups. Results: In this study, 83.6% stage III and 16.4% stage IV A. There was 62 (24.8%) upfront, 112 (44.8%) interval and 76 (30.4%) secondary group. 126 underwent cytoreductive surgery (CRS) and 124 CRS and hyperthermic intraperitoneal chemotherapy (HIPEC). There was 24.8% early and 8.4% late postop complications. Median follow up 50 months. Overall, the median disease-free survival (DFS) 39 months. PFS was 12 months among 68 patients with recurrence. Attrition rate 4%. In the upfront setting, the median DFS 44 months in CRS only group and DFS not reached (p=0.032) in CRS and HIPEC group still. In the interval setting, the median DFS 39 months in CRS only group and 44 months in CRS and HIPEC group (p=0.06). In recurrent setting, the median DFS 14 months in CRS group and 23 months in CRS and HIPEC group (p=0.02) Conclusions: Audit is an integral part of any clinical practice. It teaches us to improve the quality of care and thereby better outcomes. We recommend 6 monthly clinical audits in any cancer treatment for better outcomes in future.